2012
DOI: 10.4197/met.23-1.1
|View full text |Cite
|
Sign up to set email alerts
|

Fractures in Single-humped Camels: A retrospective Study of 220 Cases (2008-2009)

Abstract: The objective of this paper was to study the etiology and classification of fractures in dromedary camels and to evaluate their response to different treatment approaches. Two hundred and twenty cases of fractures in single-humped camels were admitted during the period from August 2008 to December 2009. On admission, special interest was given to record the cause, site, classification, radiography and outcome of treatment. Factors affecting fracture healing were studied and analyzed. Trauma was the main cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…26,29,31 The diaphysis was reported to be the most commonly affected bone segment in llamas, alpacas and camels as in our study. [26][27][28] The fracture morphology reported for llamas and alpacas was mostly comminuted fractures, which differs from our results where only 16 of 58 fractures were multi-fragmentary. 26 Similar to impala, the most common fracture morphology in camels were simple fractures.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…26,29,31 The diaphysis was reported to be the most commonly affected bone segment in llamas, alpacas and camels as in our study. [26][27][28] The fracture morphology reported for llamas and alpacas was mostly comminuted fractures, which differs from our results where only 16 of 58 fractures were multi-fragmentary. 26 Similar to impala, the most common fracture morphology in camels were simple fractures.…”
Section: Discussioncontrasting
confidence: 65%
“…26 One study done on young camels found more fractures in camels under 6 months of age, whereas another study found only 28% of fractures occurred in camels under 1 year of age. 27,28 Our study reported 40 of 58 long bone fractures occurred in skeletally immature patients; however, the low number of Salter-Harris type fractures recorded was unexpected. Our study reported 31 of 58 fractures were open compared with 32% open fractures in llamas and alpacas, and 66 to 45% compound fractures in camels.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations